A Study on the Hepatoprotective Effect of Andrographis paniculata (Burm.F) Nees on Mice - Kumar P2, Sudhakaran Sivaramakrishnan3, Sutha, Devaraj1, Jegathambigai R2* (Journal of Phytology, 2010)
Andrographis paniculata is a well known medicinal plant of Ayurveda with various pharmacological as well as medicinal properties. The present study determined the hepatoprotective effect of crude methanolic extracts of Andrographis paniculata on mice. The phytochemical screening of the crude methanolic extracts of Andrographis paniculata plant was also determined followed by the confirmation of the active compound using Thin Layer Chromatography. The hepatoprotective activity of methanolic extracts of Andrographis paniculata was evaluated against paracetamol induced (500 mg/kg) hepatic damage in mice. The extracts at doses of 10 mg/kg and 100 mg/kg were orally administered at 24 and 72 hours time interval in each group. Histological analysis of the liver and the liver protein content was determined. The results of the study indicated that the crude extracts of Andrographis paniculata at both doses exhibited a significant protective effect in the liver morphology of the paracetamol induced hepatotoxicity in mice. There was also a significant decrease (P<0.05) the liver protein content of the hepatotoxic mice after the treatments. Thin Layer Chromatography confirmed the presence of active compound, diterpene lactone or andrographolide which has contributed to the hepatoprotective activity of Andrographis paniculata. Hence, the results of the present study indicated that Andrographis paniculata possess hepatoprotective effects which could compromise the medicinal use of this plant in folk medicine. Key words: Andrographis paniculata, Hepatoprotective, Time, Liver protein <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Sutha, Devaraj et al. A Study on the Hepatoprotective Effect of Andrographis paniculata (Burm.F) Nees on Mice. J Phytol 2/11 (2010) 25-30